Synthesis of different classes of six-membered gold(I) NHC complexes by the isonitrile route - Wurm, Thomas; Mulks, Florian; Böhling, Constantin R. N.; Riedel, Dominic; Zargaran, Poorya; Rudolph, Matthias; Rominger, Frank; Hashmi, A. Stephen K. (Organometallics, 2016)
Different types of six-membered N-heterocyclic gold carbene complexes were prepared by using gold(I) isonitrile complexes as precursors in combination with suitably functionalized amines. The simple procedures provide an easy access to not only unsymmetrically substituted saturated carbene complexes but rarely reported types of carbene complexes such as six-membered N-heterocyclic oxo-carbene complexes, and six-membered partly unsaturated ligands can be obtained following the strategy.